(Invited) Electrical Activity of Extended Defects in III-V Semiconductors. (3rd July 2019) - Simoen, Eddy Roger; Hsu, P.-C.; Mols, Yves; Kunert, Bernardette; Langer, Robert; Merckling, Clement; Alian, AliReza; Waldron, Niamh; Eneman, Geert; Collaert, Nadine; Heyns, Marc; Claeys, Cor
Abstract : This paper gives an overview on the electrical activity of extended defects in III-V materials, combining different analysis methods, which are based on lifetime extraction from diode current-voltage characteristics and deep-level studies using Deep-Level Transient Spectroscopy (DLTS). To that purpose p + n junction diodes have been fabricated in In0.53 Ga0.47 As hetero-epitaxial layers on semi-insulating InP or GaAs substrates. By depositing a strained buffer layer, the Extended Defect Density (EDD) can be varied over several decades, enabling the study of the electrical impact in the same range. It will be shown that the generation and recombination (GR) lifetimes of the In0.53 Ga0.47 As layers become dominated by the EDs for densities above about 3×10 6 cm -2, whereby the dominant GR level moves closer to the mid gap position. This is supported by DLTS, showing the occurrence of specific electron traps for defective epi layers, which exhibit a capture behavior which is typical for extended defects.